DEVELOPMENT OF THE AUTOMATED SYSTEM OF PROFESSIONAL CERTIFICATION OF PERSONNEL IN THE FIELD OF CYBERSECURITY AND INFORMATION PROTECTION - Yudin, Oleksandr; Komarov, Maxim; Chernysh , Lesya; Telyushchenko, Valentina (Science-based technologies, 2025)
The article investigates modern approaches to the development and implementation of an automated system of professional certification of personnel in the field of cybersecurity and information protection. The methods and models for assessing the knowledge, skills and abilities of specialists aimed at improving the efficiency of computer testing as a key tool for assessing the knowledge, skills and abilities of specialists are considered. The authors have developed a technology for automating testing systems in terms of forming test sessions, as well as developed their own platform for computer-based testing systems based on the latest version of Moodle 4.2.3 + (modular object-oriented dynamic learning environment) for organizing and conducting testing procedures in accordance with professional standards and provide examples of practical application of the proposed solutions, including the creation of test task bases for 16 professional qualifications and testing the system based on this platform. The article pays considerable attention to data security and information protection in automated systems, including access control, user authentication, data backup, and compliance with state information security standards. The paper also describes the main shortcomings of the current state of automation of certification processes, including the lack of standardized software, low level of integration of testing systems with professional standards, and insufficient control over the assessment results. The result of the work is the formulation of recommendations for improving professional training in the field of cybersecurity in Ukraine through the introduction of an automated personnel certification system.